Heat Shock Protein 90 Triggers Multi-Drug Resistance of Ovarian Cancer via AKT/GSK3β/β-Catenin Signaling - Yin, Lan; Yang, Yuhan; Zhu, Wanglong; Xian, Yu; Han, Zhengyu; Huang, Houyi; Peng, Liaotian; Zhang, Kun; Zhao, Ye (Frontiers in Oncology, 2021)
Ovarian cancer is the most lethal gynaecologic tumor, with which multi-drug resistance as the major therapeutic hindrance. Heat shock protein 90 (Hsp90) has been involved in cancer malignant behaviours. However, its role and mechanism in multi-drug resistance of ovarian cancer remains poorly understood. Our results demonstrated that Hsp90 was overexpressed in multi-drug resistant ovarian cancer cells. Hsp90 downregulation by shHsp90 or inhibitor BIIB021 increased the sensitivity of multi-drug resistant ovarian cancer cells to paclitaxel and cisplatin, and augmented the drugs-induced apoptosis. Hsp90 positively regulated the expressions of multi-drug resistance protein 1 (P-gp/MDR1), breast cancer resistance protein (BCRP), Survivin and Bcl-2 expressions closely associated with multi-drug resistance. Moreover, overexpression of Hsp90 promoted β-catenin accumulation, while Hsp90 downregulation decreased the accumulation, nuclear translocation and transcriptional activity of β-catenin. We also identified that β-catenin was responsible for Hsp90-mediated expressions of P-gp, BCRP, Survivin and Bcl-2. Furthermore, Hsp90 enhanced the AKT/GSK3β signaling, and AKT signaling played a critical role in Hsp90-induced accumulation and transcriptional activity of β-catenin, as well as multi-drug resistance to paclitaxel and cisplatin. In conclusion, Hsp90 enhanced the AKT/GSK3β/β-catenin signaling to induce multi-drug resistance of ovarian cancer. Suppressing Hsp90 chemosensitized multi-drug resistant ovarian cancer cells via impairing the AKT/GSK3β/β-catenin signaling, providing a promising therapeutic strategy for a successful treatment of ovarian cancer.